2012
DOI: 10.5812/jjnpp.5261
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Liposomes Containing Essential Oil of Eucalyptus camaldulensis Leaf

Abstract: A B S T R A C T Background:The increased incidence of fungal resistance has necessitated the need to search for new antifungal agents. Objective: The main objectives of the present study were to investigate the effectiveness of the essential oil of Eucalyptus camaldulensis on dermatophytes growth and to formulate and characterize a liposomal gel loaded with the essential oil. Materials and Methods:The essential oil extracted from the leaves of E. camaldulensis was analyzed by GC-MS. The antifungal activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The technique seems to be useful for gradually delivering natural active substances to the site of action, for example, in medicine (Chowański et al., ) or as antimicrobial agents (São Pedro et al., ), which simultaneously minimizes the toxic effects on nontarget organisms (Campolo et al., ). Several compounds have been used for the formation of microspheres or nanoparticles that are used to deliver plant‐derived bioactive substances: liposomes (Moghimipour, Aghel, Zarei Mahmoudabadi, Ramezani, & Handali, ), oil‐in‐water nanoemulsions (Papanikolaou et al., ), Tween 20, chitosan combined with other substances (Ziaee, Moharramipour, & Mohsenifar, ), silica (Chaudhary et al., ), metals and metal oxides (Ali, Yousef, & Nafady, ), and proteins such as bovine or human serum albumins (Sokolik, Ben‐Shabat‐Binyamini, Gedanken, & Lellouche, ). Next, Athanassiou, Kavallieratos, Evergetis, Katsoula, and Haroutounian () reported the usage of a silica gel with essential oils.…”
Section: Applicationmentioning
confidence: 99%
“…The technique seems to be useful for gradually delivering natural active substances to the site of action, for example, in medicine (Chowański et al., ) or as antimicrobial agents (São Pedro et al., ), which simultaneously minimizes the toxic effects on nontarget organisms (Campolo et al., ). Several compounds have been used for the formation of microspheres or nanoparticles that are used to deliver plant‐derived bioactive substances: liposomes (Moghimipour, Aghel, Zarei Mahmoudabadi, Ramezani, & Handali, ), oil‐in‐water nanoemulsions (Papanikolaou et al., ), Tween 20, chitosan combined with other substances (Ziaee, Moharramipour, & Mohsenifar, ), silica (Chaudhary et al., ), metals and metal oxides (Ali, Yousef, & Nafady, ), and proteins such as bovine or human serum albumins (Sokolik, Ben‐Shabat‐Binyamini, Gedanken, & Lellouche, ). Next, Athanassiou, Kavallieratos, Evergetis, Katsoula, and Haroutounian () reported the usage of a silica gel with essential oils.…”
Section: Applicationmentioning
confidence: 99%
“…In a second stage, the MIC for each was established by the agar diffusion method (SDA). It was observed that the presence of the essential oil of E.camaldulensis in liposomes improved the stability of the formulation as well as its antifungal activity [36].…”
Section: Evaluation Of Topical Formulations Of Natural Productsmentioning
confidence: 99%
“…Nevertheless, the amount of essential oil associated (0.15-1.25%) is substantially lower than for nanoemulsions (up to 20%). Low amount of essential oil usually results in high association efficiency, as for Eucalyptus camaldulensis, where 0.25% of oil resulted in 95% association into lecithin/cholesterol liposomes (Moghimipour et al, 2012). The antiviral activity of Artemisia arborescens essential oil liposome was investigated in Vero cells infected with HSV-1 (Sinico et al, 2005).…”
Section: Essential Oilsmentioning
confidence: 99%